2015
DOI: 10.1016/j.jcmg.2014.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Coronary CT Angiography and Myocardial Perfusion Imaging in Kidney Transplantation Candidates

Abstract: Coronary CTA is a reliable test with high sensitivity and a high negative predictive value for diagnosing obstructive CAD before kidney transplantation. A noninvasive approach with use of either coronary CTA or a combination of coronary CTA and SPECT to rule out obstructive CAD seems recommendable in kidney transplant candidates. (ACToR-Study: Angiographic CT of Renal Transplantation Candidate-Study; NCT01344434).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 19 publications
1
66
0
2
Order By: Relevance
“…Recently, plaque assessment by coronary computed tomography angiography (CTA) showed some promise in predicting CVD outcomes among patients with CKD. 2325 In our study, inclusion of CAC score in the prediction models led to a significant increase in c-statistics and positive NRI and IDI over ACC/AHA atherosclerotic CVD risk factors and other novel risk factors. These findings suggest that CAC could be used for risk stratification and prediction among CKD patients.…”
Section: Discussionmentioning
confidence: 54%
“…Recently, plaque assessment by coronary computed tomography angiography (CTA) showed some promise in predicting CVD outcomes among patients with CKD. 2325 In our study, inclusion of CAC score in the prediction models led to a significant increase in c-statistics and positive NRI and IDI over ACC/AHA atherosclerotic CVD risk factors and other novel risk factors. These findings suggest that CAC could be used for risk stratification and prediction among CKD patients.…”
Section: Discussionmentioning
confidence: 54%
“…(2936) In a study of 138 pre-transplant candidates and using a more lenient definition of significant CAD, defined as ≥ 50% diameter stenosis, Winther et al found the sensitivity and specificity of SPECT-MPI to be 53% and 82%, respectively. (37) The reason for the relatively low diagnostic performance of SPECT-MPI in this population is multifold. First, ESRD patients have a predisposition for particular hemodynamic and anatomic abnormalities which could impair diagnostic accuracy.…”
Section: Diagnostic Accuracy Of Spect-mpi In Esrdmentioning
confidence: 99%
“…Hybrid imaging techniques, such as coronary CTA/SPECT, have been shown to enhance diagnostic performance beyond either modality alone in renal transplant patients. (37) While the advantage of positron emission tomography (PET) as compared to SPECT-MPI has been well documented in the general population,(42) the diagnostic accuracy of PET-MPI specifically in ESRD patients has not been reported in the literature.…”
Section: Diagnostic Accuracy Of Spect-mpi In Esrdmentioning
confidence: 99%
“…In a prospective study of 138 patients referred for pre-renal transplant cardiac evaluation (43% on dialysis) and underwent coronary artery calcium score, coronary computer tomography angiography, and SPECT, SPECT had a low sensitivity (53%) and modest specificity (82%) for detecting obstructive CAD (C50% stenosis). 15 Among patients with a normal SPECT, 14% of patients had obstructive CAD on invasive angiography. 15 Marwick et al found that while the sensitivity of dipyridamole thallium scintigraphy for detecting obstructive CAD was 95% in non-CKD control group, it was only 37% in dialysis patients even after matching for severity and extent of CAD.…”
Section: Stress Test In Ckd/esrd Patientsmentioning
confidence: 99%
“…15 Among patients with a normal SPECT, 14% of patients had obstructive CAD on invasive angiography. 15 Marwick et al found that while the sensitivity of dipyridamole thallium scintigraphy for detecting obstructive CAD was 95% in non-CKD control group, it was only 37% in dialysis patients even after matching for severity and extent of CAD. 16 In this study, the probability of obstructive CAD in patients with normal SPECT was 38%.…”
Section: Stress Test In Ckd/esrd Patientsmentioning
confidence: 99%